Selective inhibitors of cyclooxygenase 2 - their past, present and future - Valášková, Simona; Kyselovič, Ján; Gažová, Andrea (Ceska a Slovenska farmacie, 2023)
Pain is a serious subjective experience, which, although it has a protective nature, it physically and mentally exhausts the patient. The pharmacological field of development and research in the treatment and relief of pain has been dynamic and interesting ever since the isolation of salicylic acid. After discovering the molecular nature of cyclooxygenase and its inhibition, research focused on selective COX-2 inhibitors, but they were a big disappointment. Today, the possibility of contributing to safe and effective analgesic-antiphlogistic treatment for the patient with a combination of drugs is emerging again.
Keywords: inhibitory cyklooxygenasy 2; lidé; Cyclooxygenase 2; antiflogistika nesteroidní; cyklooxygenasa 2; cyclooxygenase inhibition; Cyclooxygenase 2 Inhibitors; Humans; Anti-Inflammatory Agents, Non-Steroidal; coxibs; Pain; non-steroidal anti-inflammatory drugs; bolest